2014
DOI: 10.4049/jimmunol.1302896
|View full text |Cite
|
Sign up to set email alerts
|

NADPH Oxidase Modifies Patterns of MHC Class II–Restricted Epitopic Repertoires through Redox Control of Antigen Processing

Abstract: The chemistries within phagosomes of APCs mediate microbial destruction as well as generate peptides for presentation on MHC class II. The antimicrobial effector NADPH oxidase (NOX2), which generates superoxide within maturing phagosomes, has also been shown to regulate activities of cysteine cathepsins through modulation of the lumenal redox potential. Using real-time analyses of lumenal microenvironmental parameters, in conjunction with hydrolysis pattern assessment of phagocytosed proteins, we demonstrated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
106
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(107 citation statements)
references
References 75 publications
(260 reference statements)
1
106
0
Order By: Relevance
“…All animal work in this study was specifically approved (M11029) by the University of Calgary Animal Care and Use Committee. BMMØs were derived from bone marrow of 8–12 week old male mice using L-929-conditioned media as a source of M-CSF over a period of 10–14 days as previously described [3034]. QPCR confirmed relative levels or absence of specific cathepsin mRNA in BMMØ cultures (S1 Protocol, S1 Fig).…”
Section: Methodsmentioning
confidence: 94%
See 3 more Smart Citations
“…All animal work in this study was specifically approved (M11029) by the University of Calgary Animal Care and Use Committee. BMMØs were derived from bone marrow of 8–12 week old male mice using L-929-conditioned media as a source of M-CSF over a period of 10–14 days as previously described [3034]. QPCR confirmed relative levels or absence of specific cathepsin mRNA in BMMØ cultures (S1 Protocol, S1 Fig).…”
Section: Methodsmentioning
confidence: 94%
“…To determine if BMMØs from cathepsin-deficient mice are capable of presenting murine MOG antigens to 2D2 CD4+ T cells, BMMØs derived from WT and cathepsin B, S, L, B/S, or S/L deficient mice were exposed to the immunodominant I-Ab epitope murine MOG 35-55 (0, 1, 10, 25 μg/ml; 0.39–9.7 nM), or to the full extracellular domain of murine MOG (MOG 1-125 ; 0, 1, 10, 25 μg/ml; 0.039–0.96 nM) [31, 34, 37, 38], for 6 h within culture medium. Cultures without BMMØs or MOG, or with concanavalin A (ConA, 5 μg/ml) treatment, were included as negative and positive controls for specific presentation and T cell proliferation respectively.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, CYBB has a controversial role in modulating phagosome maturation; some investigators find that it delays phagosomal maturation, 23,24 whereas others do not. [25][26][27] Recent studies showed that the maturation status of macrophages dictates the effects that the CYBB NADPH oxidase has on phagosome maturation. 28 Based on these findings, we hypothesize that both CYBB and ATG proteins, which are linked in phagosomal development, may have effects on phagosome maturation that are condition-dependent and possibly dynamic-altered by status of the macrophages, e.g., in classically activated macrophages (M1) vs. alternatively activated macrophages (M2).…”
Section: Discussionmentioning
confidence: 99%